2015
DOI: 10.1002/ange.201503792
|View full text |Cite
|
Sign up to set email alerts
|

Ester‐Mediated Amide Bond Formation Driven by Wet–Dry Cycles: A Possible Path to Polypeptides on the Prebiotic Earth

Abstract: Although it is generally accepted that amino acids were present on the prebiotic Earth, the mechanism by which a-amino acids were condensed into polypeptides before the emergence of enzymes remains unsolved. Here,w ed emonstrate aprebiotically plausible mechanismfor peptide (amide) bond formation that is enabled by a-hydroxy acids,which were likely present along with amino acids on the early Earth. Together, a-hydroxy acids and a-amino acids form depsipeptides-oligomers with ac ombination of ester and amide li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 32 publications
3
51
0
Order By: Relevance
“…Or, in the experiments of Kanavarioti et al (36), polymers of oligouridylates are found up to lengths of 11 bases long, with an average length of 4 after samples of phosphoimidazolide-activated uridine were frozen in the presence of metal ions in dilute solutions. Similar results are found in other polymers: a prebiotically plausible mechanism produces oligomers having a combination of ester and amide bonds up to length 14 (38).…”
Section: "Flory Length Problem": Polymerization Processes Produce Mossupporting
confidence: 85%
See 1 more Smart Citation
“…Or, in the experiments of Kanavarioti et al (36), polymers of oligouridylates are found up to lengths of 11 bases long, with an average length of 4 after samples of phosphoimidazolide-activated uridine were frozen in the presence of metal ions in dilute solutions. Similar results are found in other polymers: a prebiotically plausible mechanism produces oligomers having a combination of ester and amide bonds up to length 14 (38).…”
Section: "Flory Length Problem": Polymerization Processes Produce Mossupporting
confidence: 85%
“…Longer chains can sometimes result through adsorption to clays (31,32) or minerals (33,34), from evaporation from tidal pools (35), from concentration in ice through eutectic melts (36), or from freezing (37) or temperature cycling. Even so, the chainlength extensions are modest (38).…”
Section: "Flory Length Problem": Polymerization Processes Produce Mosmentioning
confidence: 99%
“…Models of mutualism and cooperative effects in autocatalytic sets, on quasi-species, the protein world and the RNA world (see for example, [3][4][5][6]) all assume tacitly the homochirality of the implied species. The origin of biological homochirality is thus considered as a separate and disjoint event: the formation of enantiomerically pure polymers is assumed to occur by starting from enantiomerically pure mixtures of their monomers.…”
Section: Introductionmentioning
confidence: 99%
“…We recently introduced a model prebiotic pathway for peptide formation based on ester-amide exchange reactions between α-amino acids and α-hydroxy acids (12), amino acid structural analogs found in meteorites and model prebiotic reactions (13,14) ( Fig. 1A).…”
mentioning
confidence: 99%
“…Three prebiotic amino acids, glycine (G), L-alanine (A), and L-leucine (L), were mixed with one hydroxy acid: glycolic acid (g), L-lactic acid (a), or L-malic acid (d). Each mixture contained one hydroxy acid and three amino acids (g+G+A+L, a+G+A+L, and d+G+A+L) and was subjected to one, two, or four 85°C-dry/65°C-wet cycles chosen to model a daily evaporating pool environment on the early Earth (12). The resulting nine depsipeptide libraries were examined by ultraperformance liquid chromatography -ion mobility-tandem mass spectrometry (UPLC-IM-MS/MS) in data-dependent acquisition (DDA) mode.…”
mentioning
confidence: 99%